A Hospital-based Managed Alcohol Program in a Canadian Setting. Issue 2 (22nd March 2023) - Nolan, Seonaid; Fairgrieve, Christopher; Dong, Huiru; Garrod, Emma; van Heukelom, Holly; Parappilly, Beena P.; McLean, Mark; Tsui, Judith I.; Samet, Jeffrey H.
Abstract : Objectives: A managed alcohol program (MAP) is a harm reduction strategy that provides regularly, witnessed alcohol to individuals with a severe alcohol use disorder. Although community MAPs have positive outcomes, applicability to hospital settings is unknown. This study describes a hospital-based MAP, characterizes its participants, and evaluates outcomes. Methods: A retrospective chart review of MAP participants was conducted at an academic hospital in Vancouver, Canada, between July 2016 and October 2017. Data included demographics, alcohol/substance use, alcohol withdrawal risk, and MAP indication. Outcomes after MAP initiation included the change in mean daily alcohol consumption and liver enzymes. Results: Seventeen patients participated in 26 hospital admissions: 76% male, mean age of 54 years, daily consumption prehospitalization of a mean 14 alcohol standard drinks, 59% reported previous nonbeverage alcohol consumption, and 41% participated in a community MAP. Most participants were high risk for severe, complicated alcohol withdrawal and presented in moderate withdrawal. Continuation of community MAP was the most common indication for hospital-based MAP initiation (38%), followed by a history of leaving hospital against medical advice (35%) and hospital illicit alcohol use (15%). Hospital-based MAP resulted in a mean of 5 fewer alcohol standard drinks daily compared with preadmission ( P = 0.002; 95% confidence interval, 2–8) and improvement in liver enzymes, with few adverse events. Conclusions: Participation in a hospital-based MAP may be an effective safe approach to reduce harms for some individuals with severe alcohol use disorder. Further study is needed to understand who benefits most from hospital-MAP and potential benefits/harms following hospital discharge.